A re-reading of William Parley’s telos in design within the context of anthropic principle and Its implications for contemporary theology (2020)
Philosophers and Theologians have grappled with the need to understand the nature of the universe for centuries, and for this subject to remain a subject of intense discussion in contemporary circles, suggests its continuous importance. Science has always been relevant, most significantly, in its attempt to explain our interest in the world around us. Thus, William Parley made use of the famous analogy of a watch and the world to explain the precision in the universe, and to prove the existence of a designer. This paper, therefore, attempts a re-reading of his work within the context of a scientific position known as the Anthropic Principle. This is done by focusing on William Parley’s Teleological argument for God’s existence; the nature of science and religion within the framework of this study; and lastly, the meaning of the Anthropic Principle and its implication for contemporary theology. This study employs the Providence theory of John Polkinghorne, which shows that God has created the universe in such a way as to provide what is needed for life, most especially human existence